APLIKASI PENGOLAHAN DATA ZAKAT BERBASIS WEB PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA JAMBI: APPLICATION, ZAKAT, DATA PROCESSING, WEB, BAZNAS JAMBI CITY. - Nurjani, Yeni; Robertho (LP2M STMIK Nurdin Hamzah Jambi, 2019)
The National Zakat Amil Agency (BAZNAS) is the only official body formed by the government based on RI Decree No.8 of 2001 which has the task and function of collecting and distributing zakat, infaq, and alms at the national, provincial and regional levels. Accurate and fast management of data and information can help grow an organization. Therefore, management of data and information is seen as important for the smooth running of a job and for analyzing the development of a job. During this time the processing of zakat data in the BAZNAS of Jambi City is still carried out without a special computerized system and has several disadvantages, including the susceptibility of data input errors, data damage or loss due to the absence of special data storage centers for data and files. has been inputted, to the lack of efficiency in the process of processing lecturer performance data as a whole. Web-based Zakat Data Processing Application at the National Zakat Amil Agency (BAZNAS) of Jambi City. Is a new system that was developed with the aim to facilitate the processing of zakat data as a whole and overcome the shortcomings that exist in the system that has been running. The application will be built using the PHP programming language and MySQL database management software. The application of zakat data processing that starts from the process of inputting data and related files collects and distributes zakat that can be done by the admin, then the data is stored structurally in a data storage center, until the output is in the form of reports relating to the collection and distribution of zakat. The results of this study indicate that a computerized system can improve efficiency and effectiveness in processing zakat data as a whole.